2021
DOI: 10.3892/etm.2021.10836
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of safranal on hypoxia/reoxygenation‑induced injury in H9c2 cardiac myoblasts via the PI3K/AKT/GSK3β signaling pathway

Abstract: Safranal (SFR), an active ingredient extracted from saffron, exhibits a protective effect on the cardiovascular system. However, the mechanism of SFR against hypoxia/reoxygenation (H/R)-induced cardiomyocyte injury has previously not been investigated in vitro. The aim of the present study was therefore to observe the protective effects of SFR on H/R-induced cardiomyocyte injury and to explore its mechanisms. A H/R injury model of H9c2 cardiac myoblasts was established by administering 800 µmol/l CoCl 2 to H9c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 68 publications
0
3
0
Order By: Relevance
“…Such injury is known as IRI ( 41 ). Previous studies have reported that the pathogenesis of IRI involves excessive ROS generation and inflammatory responses ( 42 , 43 ). The underlying molecular mechanisms and pathways of IRI are complicated and associated with multiple forms of regulated cell death, including pyroptosis, necroptosis, ferroptosis and apoptosis ( 44 , 45 ).…”
Section: Discussionmentioning
confidence: 99%
“…Such injury is known as IRI ( 41 ). Previous studies have reported that the pathogenesis of IRI involves excessive ROS generation and inflammatory responses ( 42 , 43 ). The underlying molecular mechanisms and pathways of IRI are complicated and associated with multiple forms of regulated cell death, including pyroptosis, necroptosis, ferroptosis and apoptosis ( 44 , 45 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, safranal, an active ingredient extracted from saffron, exerts a protective effect on the cardiovascular system. Wang H. et al (2021 ) reported that safranal could increase the viability of H9c2 cardiac myoblasts and alleviate H/R-induced H9c2 cardiac myoblast injuries via the PI3K/AKT/GSK3β signaling pathway.…”
Section: Potential Action Mechanisms Of Tcm For Cmvdmentioning
confidence: 99%
“…The latest research showed that SFR had some protective effect on the heart. For example, Wang H, et al thought that SFR exerted protective effect against hypoxia/reoxygenation -induced cardiomyocyte injury via inhibiting oxidative stress and apoptosis [10]. Mehdizadeh R, et al, revealed that SFR played cardio-protective on myocardial infarction by inhibitting of oxidative stress and regulating Ca2+ homeostasis [11,12].…”
Section: Introductionmentioning
confidence: 99%